Vulnerability to chronic stress and the phenotypic heterogeneity of presbycusis with subjective tinnitus - Ruan, Jian; Hu, Xiuhua; Liu, Yuehong; Han, Zhao; Ruan, Qingwei (Frontiers in Neuroscience, 2022)
Age-related functional reserve decline and vulnerability of multiple physiological systems and organs, as well as at the cellular and molecular levels, result in different frailty phenotypes, such as physical, cognitive, and psychosocial frailty, and multiple comorbidities, including age-related hearing loss (ARHL) and/or tinnitus due to the decline in auditory reserve. However, the contributions of chronic non-audiogenic cumulative exposure, and chronic audiogenic stress to phenotypic heterogeneity of presbycusis and/or tinnitus remain elusive. Because of the cumulative environmental stressors throughout life, allostasis systems, the hypothalamus-pituitary-adrenal (HPA) and the sympathetic adrenal–medullary (SAM) axes become dysregulated and less able to maintain homeostasis, which leads to allostatic load and maladaptation. Brain–body communication via the neuroendocrine system promotes systemic chronic inflammation, overmobilization of energetic substances (glucose and lipids), and neuroplastic changes via the non-genomic and genomic actions of glucocorticoids, catecholamines, and their receptors. These systemic maladaptive alterations might lead to different frailty phenotypes and physical, cognitive, and psychological comorbidities, which, in turn, cause and exacerbate ARHL and/or tinnitus with phenotypic heterogeneity. Chronic audiogenic stressors, including aging accompanying ontological diseases, cumulative noise exposure, and ototoxic drugs as well as tinnitus, activate the HPA axis and SAM directly and indirectly by the amygdala, promoting allostatic load and maladaptive neuroplasticity in the auditory system and other vulnerable brain regions, such as the hippocampus, amygdala, and medial prefrontal cortex (mPFC). In the auditory system, peripheral deafferentation, central disinhibition, and tonotopic map reorganization may trigger tinnitus. Cross-modal maladaptive neuroplasticity between the auditory and other sensory systems is involved in tinnitus modulation. Persistent dendritic growth and formation, reduction in GABAergic inhibitory synaptic inputs induced by chronic audiogenic stresses in the amygdala, and increased dendritic atrophy in the hippocampus and mPFC, might involve the enhancement of attentional processing and long-term memory storage of chronic subjective tinnitus, accompanied by cognitive impairments and emotional comorbidities. Therefore, presbycusis and tinnitus are multisystem disorders with phenotypic heterogeneity. Stressors play a critical role in the phenotypic heterogeneity of presbycusis. Differential diagnosis based on biomarkers of metabonomics study, and interventions tailored to different ARHL phenotypes and/or tinnitus will contribute to healthy aging and improvement in the quality of life.